Carbon dots with tailor-made chelating ligands for specific metal ions recognition: Target synthesis and prediction of metal ions selectivity. (31st October 2022) - Dong, Jiaxin; Li, Baoqiang; Xiao, Jin; Liu, Guanxiong; Baulin, Vladimir; Feng, Yujie; Jia, Dechang; Tsivadze, Aslan Yu; Zhou, Yu
Abstract: Carbon dots (CDs) have been widely applied in metal ion recognition and detection, which makes them promising in the fields of environmental monitoring and biomedical science. However, CDs usually contain multiple functional groups that have different affinities for metal ions, so the relationship between CDs and recognized metal ions is ambiguous, which limits the prediction of recognized metal ions. Herein, CDs with different chelating ligands were target synthesized via free radical polymerization in combination of hydrothermal carbonization technology, the precursors directional converted into CDs. The tailor-made CDs with ethylenediamine tetraacetic acid (EDTA, EfCDs) and hydroxyethylidene diphosphonic acid (HEDP, HfCDs) chelating ligands were synthesized with high synthetic yields of 86.7% and 72.5%, respectively. The coordination constant ( K ) and the number of chelation site ( n ) of EfCDs for Fe 3+ were (3.92 ± 0.03) × 10 4 M −1 and 3.62 ± 0.18, while the values of K and n of HfCDs for Cu 2+ were (5.95 ± 0.04) × 10 5 M −1 and 1. EfCDs and HfCDs can serve as fluorescence probes for specific recognition of Fe 3+ and Cu 2+, respectively. Based on the metal-chelating affinity of EDTA and HEDP for Fe 3+ and Cu 2+ (lgKEDTA-Fe = 25.1, lgKHEDP -Cu = 12.5), EfCDs and HfCDs were predicted to specifically recognize Fe 3+ and Cu 2+ . We established the exponential type functions between fluorescence quenching degree ( 1-F/F 0 ) and coordination constant ( lgK ) of EDTA or HEDP to facilitate the prediction of specific recognition of metal ions. This study proposes a new strategy for heavy metal ions specific recognition using CDs with tailor-made chelating ligands. Graphical abstract: Carbon dots with different chelating ligands were target synthesized via free radical polymerization in combination of hydrothermal carbonization technology, in which precursors were directional converted into carbon dots. The chelate functionalized carbon dots modified with EDTA and HEDP can achieve specific recognition of Fe 3+ and Cu 2+ and enhanced magnetic resonance imaging. Image 1 Highlights: Target synthesis of CDs via free radical polymerization and carbonization process. The coordination constant and chelation sites of functionalized CDs were calculated. Established exponential type functions between lgK and ( 1-F/F 0 ). Predicted and confirmed CDs with EDTA and HEDP specifically recognize Fe 3+ and Cu 2+ .